Neoliberal gothic : international gothic in the neoliberal age - Blake, Linnie; Monnet, Agnieszka Soltysik; Manchester University Press (Manchester, UK : Manchester University Press, 2017)
The explosion of interest in the gothic in recent years has coincided with a number of seismic political changes that have reshaped the world as we know it. 'Neoliberal Gothic' explores that world, considering the ways in which the exponential increase in the cultural visibility of the gothic attests to the mode's engagement with the most significant dynamics of our age. These include the triumph of free market economics, the revolution in information and communication technologies, the emergence of global biotechnologies, the increasing power of transnational corporations, the US-led 'War on Terror' and the global financial crisis of 2008. Through analysis of texts drawn from literature, film, television, theatre and the visual arts (from the Europe to South East Asia, Africa to North and South America) the collection examines the ways in which the representational strategies of the gothic mode are ideally suited to an exploration of the dark side of neoliberal enterprise.
Introduction: neoliberal gothic - Linnie Blake and Agnieszka Soltysik MonnetPart I: Neoliberal gothic monsters1. Game of fangs: the vampire and neoliberal subjectivity -- Aspasia Stephanou2. Austerity bites: refiguring Dracula in a neoliberal age -- Stephanie Genz3. Staging spectrality: capitalising (on) ghosts in German postdramatic theatre -- Barry MurnanePart II: Biotechnologies, neoliberalism and the gothic4. The return of the dismembered: Representing organ trafficking in Asian cinemas - Katarzyna Ancuta5. Catastrophic events and queer northern villages: Zombie pharmacology In the Flesh - Linnie Blake6. Gothic vulnerability: affect and ethics in fiction from neoliberal South Africa -- Rebecca Duncan Part III: The gothic home and neoliberalism7. Market value: American Horror Story's housing crisis -- Karen E. Macfarlane8. Haunted by the ghost: from global economics to domestic anxiety in contemporary art practice -- Tracy FaheyPart IV: Crossing borders9. Gothic meltdown: German nuclear cinema in neoliberal times -- Steffen Hantke10. Border Gothic: Gregory Nava's Bordertown and the dark side of NAFTA -- Agnieszka Soltysik MonnetIndex.
Includes bibliographical references and index.
Students and academics in Gothic Studies, contemporary literary, televisual and film studies.
In English.
Print version record version and e-Publication, viewed on August 7, 2018
JSTOR
Keywords: Gothic fiction (Literary genre) -- History and criticism; Neoliberalism; Gothic literature -- History and criticism; Néo-libéralisme.; Littérature gothique -- Histoire et critique; Society and social sciences; Cultural studies; LITERARY CRITICISM -- Gothic & Romance; Neoliberalism; Gothic literature; Gothic fiction (Literary genre); Biography, Literature & Literary studies; Electronic books; Criticism, interpretation, etc